Valuing the investigation of Prion diseases in Ethiopia - Eden Yitna Teferedegn; Tesfaye D; Ün C (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2019)
Cellular Prion proteins have a wide variety of function from the birth of a cell to its programmed death. Prion protein can be the cause for a number of lethal animal and human diseases when misfolded. Furthermore, prion infection is transmissible. Polymorphisms of prion gene at different loci are associated with prion diseases development, the onset of symptoms and incubation period. Indel polymorphism in the promoter region of PRNP gene is found to be accoaited to BSE in cattle while the haplotype ARR at positions 136,154 and 171 is resistant to scrapie in sheep. Taking into account the severity of prion disease and its potential entrance to the food chain, genetic and clinical studies continued to be conducted in a different course of time in many countries. Even though African countries in general and Ethiopia in particular, are highly dependent on animals and animal products as food and income source, there are neither epidemiologic nor genetic studies addressed prion diseases yet. Moreover, high animal product consumption and poor regular animal health inspection are among the many good reasons to study prion in Ethiopia. Prion disease survey and prion gene profiling boldly contribute to the provision of prion-free animals to the market for local consumption and for export. Thus, the main objective of this work is to uncover the extent of the importance of prion-related studies in Ethiopia considering livestock management, food quality safeguard and contribution of the work for further study.